Ответы и объяснения

2012-04-07T12:57:40+04:00

Упростим выражение:

3/(x+2)=7/(x-1)

Составим пропорцию:

7(x+2)=3(x-1)

7x+14=3x-3

4x=-17

x=-17/4

x= -4 1/4

Лучший Ответ!
2012-04-07T13:05:51+04:00

3/(x+2) = 4+3/(x-1)                        ОДЗ:  x+2 ≠ 0    и  x-1 ≠ 0

                                                                    x ≠ - 2  и  x ≠ 1

3/(x+2) = 4 + 3/(x-1)    |  *(x+2)*(x-1)

3*(x-1) = 4*(x+2)*(x-1)  +  3 *(x+2)

3х - 3  = 4(х² -х + 2х -2) + 3х + 6

3х - 3  = 4(х² + х - 2) + 3х + 6

3х - 3  = 4х² + 4х - 8 + 3х + 6

3х - 3  = 4х² + 7х - 2

 4х² + 7х - 2 - 3х + 3  = 0

 4х² + 4х + 1 = 0

D = 16 - 4*4  16 -16 = 0

х₁ = х₂ = - 4/8 = - 1/2  (удовлетворяет ОДЗ)

 

Ответ:  - 1/2.